Patient satisfaction in a home-based capillary blood glucose self-monitoring educational program - Denise Ferro; Vivian Saraiva Veras; Flávia Fernanda Luchetti Rodrigues; Tatiane Aparecida Martins; Carla Regina de Souza Teixeira; Manoel Antônio dos Santos; Maria Lucia Zanetti (Universidade Federal de Goias, 2015)
The aim of this cross-sectional study was to assess the satisfaction of patients with diabetes mellitus (DM) after being provided with an educative program for self-monitoring capillary glucose at home. The convenience sample was made of 29 patients, from two basic health units in a city in the interior of São Paulo, in 2012. Patient satisfaction regarding the diabetes education group was assessed using a questionnaire and a form containing sociodemographic variables. Results showed that most of the patients considered the educative program to be excellent/satisfactory. Regarding the information received, the patients stated it met their needs and that they would recommend the program to other people. In conclusion, investments are needed so that the educative programs provided in health services to people with DM are permanently assessed and use satisfaction as an assessment indicator.